2000
DOI: 10.1016/s0168-6496(99)00100-2
|View full text |Cite
|
Sign up to set email alerts
|

Francisella tularensis does not manifest virulence in viable but non-culturable state

Abstract: Francisella tularensis is a small Gram‐negative bacterium that causes tularemia in animals and man. The disease can be transmitted by handling of infected animals, by contaminated dust, by insect vectors, or by drinking contaminated water. In the present study cells of F. tularensis were subjected to extended storage in cold water devoid of carbon sources. Total cell counts remained constant throughout a 70‐day period and beyond, while plate counts decreased to an undetectable level after 70 days. Attempts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…Following literature reports of improved survival at 8°C (Jellison et al. 1950; Forsman et al. 2000), the F. tularensis experiments thereafter were conducted only at 8°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following literature reports of improved survival at 8°C (Jellison et al. 1950; Forsman et al. 2000), the F. tularensis experiments thereafter were conducted only at 8°C.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers conducting similar work with F. tularensis were successful with culture at 8°C and hypothesize that 8°C is closer than 5 or 25°C to temperatures found in mountain streams, a habitat in which the organism is commonly found (Jellison et al. 1950; Forsman et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only live bacteria residing in the salivary glands would be immediately available for transmission via tick bite. The agent of tularemia also is known to enter a viable but non-cultivatable (VBNC) and presumably non-infectious state in the environment (Forsman et al, 2000), and it is possible that tick-bound F. tularensis is similarly in a VBNC state. On the other hand, homogenates of ticks containing F. tularensis DNA are capable of infecting mice and causing disease when injected; and, the agent may be recovered from such homogenates by cultivation on CHAB (Hopla, 1960).…”
Section: Discussionmentioning
confidence: 99%
“…F. tularensis subsp. tularensis is the more virulent subspecies and, with few exceptions (Johansson et al 2000, Guryčová 1998), it has been reported only from North America. F. tularensis subsp.…”
Section: The Organismmentioning
confidence: 99%